Disease Interpretations and Response among HIV-positive Mothers - Johanna Debora Imelda (Antropologi Indonesia, 2014)
Despite the growing number of new cases of HIV and AIDS in Indonesia, the progress ofprevention programs has been slow. Low prevalence is always stated as a reason for delayingHIV prevention programs and to justify slow progress in implementation. Prevention programsare moreover based on a high-risk group paradigm. They focus on female sex workers asresponsible for the spread of HIV, leading to its stigmatization as a hooker’s disease. This articledescribes how seropositive mothers interpret and respond to HIV and AIDS as women, in lightof the fact that most of them have not experienced full-blown AIDS. Some women had alreadyexperienced severe illnesses caused by HIV but defined their ill health by the symptoms theyexperienced, revealing that they did not really feel as if they were living with HIV and AIDS.Despite the fact that some members had died due to AIDS, many still could not believe thatthey were suffering from HIV and AIDS or that their illnesses were caused by it; rather, theirsymptoms were of other diseases such as diarrhoea, tuberculosis, or hepatitis. And thoughthey realized that their past (or present) behaviours put them at risk, they maintained thatthey were victims who had contracted the disease from their promiscuous or drug-injectinghusbands. Even when they did admit that their own behaviour had something to do with it,they did not consider HIV and AIDS as a disease but a curse from God, a punishment fortheir immoral behaviour.Keywords: Women, Infectious Disease, Interpretation, HIV and AIDS, Support Group,Indonesia